2021
DOI: 10.31234/osf.io/279yg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scientists, speak up! Source impacts trust in health across five countries

Abstract: We examined how different types of communication influence people’s responses to health advice. Specifically, we tested whether presenting Covid-19 prevention advice (i.e., washing hands) as either originating from the government or a scientific source would affect people’s trust and intentions to comply with the advice. We also tested the effects of uncertainty framing: We presented the advice as being either certainly or potentially effective in reducing virus spread. To achieve this, we conducted an experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…People tend to employ a common heuristic to trust scientists (Hmielowski et al, 2014), a wellestablished finding called "the Einstein effect" that was recently replicated in a large cross-cultural study (Hoogeven et al, 2022). Other research had similar results and showed that respondents had more trust in messages shared by scientific sources than in messages shared by the government (Zarzeczna et al, 2021), and 73% of the public's views on the COVID-19 pandemic matched the views of scientists (Rothmund et al, 2020). Although trust in science and scientists appears to be a common heuristic, the presence of individuals with high science skepticism on critical issues like pandemics, climate change, anti-vaccination, and engaging in pseudoscientific practices sparked an interest in research on science skepticism and trust in science (e.g., Rutjens et al, 2021;Scheitle et al, 2021;Većkalov et al, 2022), and the negative consequences of distrust in science and scientists, such as lower adherence to preventive measures during the COVID-19 pandemic (Erisen, 2022;Dohle et al, 2020;Plohl et al, 2020;Sulik et al, 2021) and lower levels of vaccination (Cavojova et al, 2021;Erisen, 2022;Lalot et al, 2021;Slotte et al, 2022;Zezelj et al, 2021).…”
Section: Highly Corrupt Countriesmentioning
confidence: 66%
“…People tend to employ a common heuristic to trust scientists (Hmielowski et al, 2014), a wellestablished finding called "the Einstein effect" that was recently replicated in a large cross-cultural study (Hoogeven et al, 2022). Other research had similar results and showed that respondents had more trust in messages shared by scientific sources than in messages shared by the government (Zarzeczna et al, 2021), and 73% of the public's views on the COVID-19 pandemic matched the views of scientists (Rothmund et al, 2020). Although trust in science and scientists appears to be a common heuristic, the presence of individuals with high science skepticism on critical issues like pandemics, climate change, anti-vaccination, and engaging in pseudoscientific practices sparked an interest in research on science skepticism and trust in science (e.g., Rutjens et al, 2021;Scheitle et al, 2021;Većkalov et al, 2022), and the negative consequences of distrust in science and scientists, such as lower adherence to preventive measures during the COVID-19 pandemic (Erisen, 2022;Dohle et al, 2020;Plohl et al, 2020;Sulik et al, 2021) and lower levels of vaccination (Cavojova et al, 2021;Erisen, 2022;Lalot et al, 2021;Slotte et al, 2022;Zezelj et al, 2021).…”
Section: Highly Corrupt Countriesmentioning
confidence: 66%
“…People tend to employ a common heuristic to trust scientists (Hmielowski et al, 2014), a well-established finding called “the Einstein effect” which was recently replicated in a large cross-cultural study that assessed the perceived credibility of a scientist (compared to a spiritual guru) in 24 different countries (Hoogeveen et al, 2022). Other research, for instance, by Zarzeczna and colleagues (2021), using representative samples from various countries (i.e. United Kingdom, United States, Canada, Malaysia, and Taiwan), found similar results: across different countries, respondents had more trust in messages shared by scientific sources than in messages shared by the government (Zarzeczna et al, 2021).…”
mentioning
confidence: 70%
“…Other research, for instance, by Zarzeczna and colleagues (2021), using representative samples from various countries (i.e. United Kingdom, United States, Canada, Malaysia, and Taiwan), found similar results: across different countries, respondents had more trust in messages shared by scientific sources than in messages shared by the government (Zarzeczna et al, 2021). Finally, in a study conducted in Germany, it was found that 73% of the population's views on the COVID-19 pandemic matched the views of scientists (Rothmund et al, 2020).…”
mentioning
confidence: 72%
“…In addition, recent research also suggests it is important to consider how scientists are portrayed in science communication. For example, recent work has found that scientists are seen as more trustworthy sources of advice on COVID-19-related measures as opposed to government officials [56]. Moreover, emphasizing communal (vs. self-oriented) motivations of scientists elicited greater trust and funding support [57].…”
Section: Curbing (Conspiratorial) Science Rejectionmentioning
confidence: 99%